2006
DOI: 10.1111/j.1445-5994.2006.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of multidisciplinary care teams for acutely ill medical inpatients: enhanced multidisciplinary care

Abstract: This model of enhanced multidisciplinary inpatient care has provided sustainable efficiency gains for the hospital and improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 19 publications
1
50
0
2
Order By: Relevance
“…Hospital-based PT was associated with reductions in early hospital readmission rate. Although several previous studies have confirmed functional responses to hospital-based PT [13][14][15]19], these were limited to stroke and hip fracture patients. Our study contributes to the literature by providing evidence that PT reduces progressive functional decline, even in common acute illness (pneumonia).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hospital-based PT was associated with reductions in early hospital readmission rate. Although several previous studies have confirmed functional responses to hospital-based PT [13][14][15]19], these were limited to stroke and hip fracture patients. Our study contributes to the literature by providing evidence that PT reduces progressive functional decline, even in common acute illness (pneumonia).…”
Section: Discussionmentioning
confidence: 98%
“…To reduce or delay functional decline during or after hospitalization, physical therapy (PT) has been utilized as an independent rehabilitation measure and a component of multidisciplinary care [14][15][16]. PT to restore functional reserve has been applied to certain acute illness, such as stroke and hip fracture, with excellent rehabilitation potential in both acute and post-acute hospital settings [13,14].…”
Section: Aging and Disease • Volume 6 Number 3 June 2015 175mentioning
confidence: 99%
“…A 1993 meta-analysis reported that inpatient CGA and GEM significantly improve patients' survival (after 6 months) and functional autonomy (after 12 months). [126][127][128][129][130][131][132][133] DISCUSSION This report and its Web supplement constitute a catalog of the positive studies of 15 successful care models for older Americans with chronic conditions. Each of these models provides comprehensive health care for older patients and was deemed successful, because at least one high-quality study reported that at least one version of the model is capable of improving the quality, outcomes, or efficiency of care (compared with ''usual care'').…”
Section: Interdisciplinary Primary Carementioning
confidence: 96%
“…28 Compared with usual care control medical wards, intervention wards demonstrated no difference in readmissions. Similar results were noted in a randomised trial of interdisciplinary ward rounds involving 1102 general medical patients.…”
Section: Multidisciplinary Teams and Ward Roundsmentioning
confidence: 99%